Long-Term Follow-Up Results of a Patient Undergoing Acute Retinal Necrosis: A Case Report and Literature Review - Büşra Köse; Hidayet Erdöl; Dilek Uzlu (Case Reports in Ophthalmological Medicine)
Purpose. To describe the follow-up and treatment approach of a patient with acute retinal necrosis. Case Report. A 44-year-old male patient, who had complaints of pain in the right eye and blurred vision, was referred to our clinic. Best-corrected visual acuity (BCVA) was 0.4. There was 2+ anterior chamber reaction and diffuse smooth-rounded keratic precipitates. Fundus examination revealed optic nerve and vascular involvement. Fundus fluorescein angiography revealed extensive ischemia in the periphery. Oral antiviral therapy was preferred. In addition, systemic steroid and laser photocoagulation were applied. Nonetheless, retinal detachment developed 2 months later. Detachment, silicon removal, and cataract surgery were performed sequentially. It was observed that the patient was followed for 4.5 years and did not have contralateral eye involvement. Best-corrected visual acuity remained stable at 0.3. Conclusion. Early diagnosis, appropriate treatment, accurate complication management, and frequent follow-up may provide useful vision in patients with acute retinal necrosis.